2010
DOI: 10.1099/mic.0.034066-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide induces apoptosis-like death in Entamoeba histolytica trophozoites

Abstract: Programmed cell death (PCD) is an essential process in the growth and development of multicellular organisms. However, accumulating evidence indicates that unicellular eukaryotes can also undergo PCD with apoptosis-like features. This study demonstrates that after exposure to 0.8 mM H 2 O 2 for 9 h Entamoeba histolytica presents morphological and biochemical evidence of apoptosis-like death. Morphological characteristics of apoptosis-like death including DNA fragmentation, increased vacuolization, nuclear cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 74 publications
(62 reference statements)
2
21
2
Order By: Relevance
“…An hypothetical model for the pathway of apoptosis could be that • OH stimulates Ca 2 þ influx that triggers calpain activities, which in turn cleaves Bid or Bax that induces the release of cytochrome c with subsequent caspase-9 and caspase-3 activation that results in DNA fragmentation in fish erythrocytes. Nevertheless, Nandi et al revealed that H 2 O 2 induces a distinct calpain-dependent DNA fragmentation without the involvement of caspases in E. histolytica trophozoites [99]. Furthermore, our results showed that zVAD-fmk completely prevented the caspase-9 and caspase-3 activation, but did not fully inhibited DNA fragmentation in the • OH-induced carp erythrocytes.…”
Section: • Oh-induced Apoptosis In Fish Erythrocytescontrasting
confidence: 68%
“…An hypothetical model for the pathway of apoptosis could be that • OH stimulates Ca 2 þ influx that triggers calpain activities, which in turn cleaves Bid or Bax that induces the release of cytochrome c with subsequent caspase-9 and caspase-3 activation that results in DNA fragmentation in fish erythrocytes. Nevertheless, Nandi et al revealed that H 2 O 2 induces a distinct calpain-dependent DNA fragmentation without the involvement of caspases in E. histolytica trophozoites [99]. Furthermore, our results showed that zVAD-fmk completely prevented the caspase-9 and caspase-3 activation, but did not fully inhibited DNA fragmentation in the • OH-induced carp erythrocytes.…”
Section: • Oh-induced Apoptosis In Fish Erythrocytescontrasting
confidence: 68%
“…This is in good line with the report that oxidative stress leads to the influx of Ca 2? that activates calpain with subsequent DNA fragmentation in E. histolytica trophozoites (Nandi et al 2010). Nevertheless, no reports have published the caspase-3 independent but calpain-dependent DNA fragmentation in fish cells.…”
Section: Discussionmentioning
confidence: 99%
“…This recent finding adds weight to the speculation of Debrabant and colleagues [83] that caspase-dependent and caspase-independent pathways may exist in different Leishmania spp. In addition, it has been proposed that a clan CA cysteine protease forms part of the apoptosis molecular pathway in P. falciparum [80], and calpain activity has been linked to apoptosis in E. histolytica [84]. There is no reason to exclude the possibility that cascades involving more than one clan of cysteine proteases may operate in the execution of apoptosis in some parasitic protozoans…”
Section: Reviewmentioning
confidence: 99%
“…Despite their lack of mitochondria, the parasitic protozoans Giardia intestinalis, Entamoeba histolytica , Tritrichomonas foetus and T. vaginalis can be induced to exhibit some apoptosis features, such as chromatin condensation, translocation of phosphatidylserine to the outer leaflet of the plasma membrane, DNA fragmentation, and the formation of apoptotic bodies which, in some cases, are inhibited by pancaspase inhibitors [60,84,102]. This also brings into question theories that associate the origin of apoptosis in eukaryotes with the progenitors of mitochondria.…”
Section: Reviewmentioning
confidence: 99%